PERAN KEPEMIMPINAN KEUCHIK DALAM PEMBANGUNAN DI GAMPONG JAMBAK, KECAMATAN PANTE CEUREUMEN, KABUPATEN ACEH BARAT - Aduwina Pakeh (Universitas Teuku Umar, 2017)
The purpose of this research is to know and analyze the leadership of village head in development in Jambak village, Pante Ceureumen District, West Aceh Regency and to identify how the success rate of Jambak village development in terms of physical development and non-physical development. The research method used is qualitative descriptive method with research focus among others development of education facilities, bridge facilities, road facilities, electricity facilities, training courses of village government institutions, PKK development courses, and the development of art and culture. Primary data sources in this study were village head, village secretary, community, and community leaders in Jambak village.The results obtained by the authors in showing the leadership of the village head in the development of the village of Jambak is still lacking and can not say good, because there is still a lot of work that includes physical development and non-physical development of Jambak village has not all been resolved properly. Like the construction of educational facilities that are still said to be quite good. Bridge facilities that have not been built all in accordance with community expectations. Road construction has not been fully resolved yet, electricity facilities are also a problem faced by Jambak villagers. In addition to the non-physical development of the village, the training of village institutions has been running but still ineffective to further improve the quality of village government officials, so that village government officials are more comfortable. Keywords: Leadership, Village Head, Development, Village